A Sustainable synthesis, eco-safe approach efficiency and DFT study of novel 5,6,7,8-Tetrahyroquinazolin-2(1H)-one derivatives as antioxidant reagents - Mohammed Abed Kadhim; Amin Farouk Mohamed Fahmy; Emad Khelil Mohammed Zangana; Aya Ibrahim Hassaballah; Sameh Ahmed Rizk (Indonesian Journal of Chemistry, 2023)
5,6,7,8-Tetrahydroquinazolin-2-(thio)-ones (THQ) fits the class of N-heterocycles as a structural core in numerous bioactive compounds. They promptly extended previous decades. They were significantly recognized in combinatorial chemistry and materials science to determine the drug discovery, antioxidants, and pharmaceuticals fields. In the present work, one-pot multicomponent sustainable synthesis of THQ with easily accessible starting materials, i.e., cyclohexanone, different aromatic aldehydes and (thio)urea, has been performed to determine the proposed Biginelli mechanism that is supported by DFT. It is found that the THQs are synthesized by a mechano-chemical (grinding) tool to achieve a yield of 85.2% within 3.5 min, i.e., YE (% yield/time) 24.34 differs from the conventional method in which lower % yield (YE = 0.72) of THQ was achieved. This confirmed that in the green chemistry principle, the determination of % yield according to saving reaction time must be considered. Moreover, DFT-based antioxidant properties of the THQ were also studied in which the most potent antioxidant compounds were 7b > 6d > 2f. Softness (σ, eV−1) and hardness (η, eV mol−1) can approve the soft molecule that stays more reactive as a result of decreasing the energy gap along heterocyclic with values 0.1491 > 0.1300 > 0.1168 eV−1 one-to-one with the efficiency of antioxidant.